Graft-modified polyvinyl alcohol, optical film, and method for producing same
Patent Information
- Application Number
- CN202611179214.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-13
AI Technical Summary
[0009]针对现有 PVA 光学膜依赖小分子多元醇增塑导致槽液污染,以及现有高分子共混改性方案增塑剂仍存在迁移风险、无法从根源消除溶出污染的缺陷,本发明提供一种接枝改性聚乙烯醇、其制备方法及由其制得的无小分子多元醇增塑 PVA 光学膜
Smart Images

Figure SMS_2 
Figure QLYQS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to the technical field of preparation of optical-grade polymer film materials, and specifically relates to a graft-modified polyvinyl alcohol (PVA), a preparation method thereof, and a small-molecule polyol plasticizer-free PVA optical film made from the graft-modified PVA, which is mainly applied to the production of core polarizing film materials for polarizers matched with liquid crystal displays (LCD) or organic light-emitting diode (OLED) displays. BACKGROUND ART
[0002] Polyvinyl alcohol (PVA) optical film is the core base material for manufacturing polarizers, and the mainstream industrial preparation process is the aqueous solution casting method. The polyvinyl alcohol molecular chain is rich in a large number of hydroxyl groups, with extremely high intramolecular and intermolecular hydrogen bond density. Pure PVA film has high brittleness and low tensile elongation at break, and cannot meet the requirements of continuous processes of swelling, stretching and iodine dyeing. Therefore, small-molecule polyols such as glycerol, ethylene glycol and propylene glycol are used as plasticizers in conventional formulations for manufacturing PVA optical films. Small-molecule polyols have low molecular weights, can be inserted between PVA molecular chains to increase the free volume between chains, and significantly improve the elongation at break and processing flexibility of the films, and are currently common plasticizers in the industry.
[0003] In conventional formulations, small-molecule plasticizers have certain defects. Small-molecule polyols such as glycerol and ethylene glycol have extremely high water solubility. After the PVA optical film enters the polarizer swelling tank and iodine dyeing tank, the small molecules in the film quickly dissolve into the tank liquid. The plasticizer will undergo a complexation reaction with the iodine solution, continuously consuming elemental iodine, causing the iodine solution to become turbid and the dyeing depth to be uneven, which directly reduces the polarization uniformity of the polarizer and the product yield. To maintain dyeing stability, the production line needs to frequently replace the entire set of iodine solution and swelling solution, and waste liquid treatment and raw material loss bring extremely high production costs. At the same time, small molecules will continuously migrate and precipitate to the film surface during storage, and the haze will continue to rise after long-term storage of the film, leading to deterioration of optical properties.
[0004] In order to solve the dissolution problem and ensure or improve the stretch resistance of the formed film, the industry has carried out targeted work on improvements in formulations, raw materials and other aspects. For example, a composite plasticizer of a polyol compound and a borate ester compound is added to the PVA film, and the boric acid generated by hydrolysis of the borate ester forms a complex with the polyol to inhibit its migration and exudation. However, the essence of this solution still relies on small-molecule polyols (such as glycerol) as the main plasticizer, and the borate ester only plays a role of "complexation delay" rather than "complete eradication". In the long-term hot water soaking and iodine dyeing processes of the polarizer manufacturing process, the small-molecule polyols will still be slowly released, and the problem of tank liquid pollution cannot be fundamentally solved; at the same time, the cross-linking reaction between boric acid and PVA is irreversible, and an excessively high cross-linking degree will occupy hydroxyl sites, inhibiting the adsorption and complexation of iodine, which directly affects the polarization performance of the polarizer.
[0005] Alternatively, PVA can be modified using ethylene units. For example, a small amount of ethylene monomer can be copolymerized with vinyl acetate via free radical initiation followed by alcoholysis to obtain modified PVA containing ethylene segments; or ethylene monomer can be grafted onto PVA resin for modification. On the one hand, the introduction of ethylene reduces the rigidity of the PVA molecular chain by diluting the hydrogen bond density between PVA chains, thereby improving the tensile strength of the film and meeting the requirements of optical film applications with higher strength requirements. On the other hand, the hydrophobic ethylene segments can reduce the water absorption of the PVA film, improve the film's hygrothermal stability, and ensure the processability of thin PVA optical films. However, this approach has certain limitations: due to the randomness of macromolecular free radical addition polymerization during free radical polymerization, the ethylene units are randomly distributed in the modified PVA segments rather than arranged in a regular pattern, and the ethylene units do not have the ability to complex iodide ions, which poses a risk of uneven dyeing in subsequent polarizer manufacturing processes, affecting the consistency of polarization performance. In addition, the leaching substances of PVA optical films produced by conventional formulas after being immersed in water include not only small molecule polyol plasticizers, but also some low molecular weight PVA segments. These low molecular weight components are also easily dissolved in hot water.
[0006] Alternatively, poly(meth)acrylate with hydrophilic alcohol hydroxyl groups can be physically blended with PVA. While this can partially replace small-molecule plasticizers in PVA optical film manufacturing, the plasticizer and PVA are only bonded by intermolecular hydrogen bonds, not chemical bonds. Therefore, there is still a risk of plasticizer migration and leaching during hot water immersion and long-term use, failing to address the problem of bath contamination at its source. Furthermore, poly(hydroxyethyl) methacrylate (PHEMA) has hydrophobic methyl groups on its side chains. High-molecular-weight PHEMA is insoluble in hot water, only absorbing water and swelling. This makes it unsuitable for use with all-aqueous PVA casting solutions, easily leading to phase separation, film surface mottling, and a significant increase in haze after mixing.
[0007] Although there is a large body of academic literature on graft modification of PVA resin, in the field of PVA optical film manufacturing, there is currently no technical solution that completely eliminates small molecule polyol plasticizers by grafting and polymerizing hydroxyalkyl acrylate monomers onto the PVA backbone to form a chemically bonded plasticizing system, while simultaneously achieving high elongation at break and extremely low water solubility.
[0008] This invention uses graft polymerization to covalently anchor plasticizing components containing hydroxyalkyl side chains onto the PVA backbone. This not only eliminates the leaching of small molecule plasticizers at the source, but also allows the hydroxyl groups at the ends of the hydroxyalkyl side chains to complex iodide ions, better adapting to the development trend of thinner and lower-dissolution PVA optical films. At the same time, graft polymerization increases the proportion of high molecular weight segments, making the film less prone to dissolution after being immersed in water. The overall performance is significantly better than existing technical solutions. Summary of the Invention
[0009] To address the shortcomings of existing PVA optical films, which rely on small-molecule polyol plasticizers leading to bath contamination, and the inherent migration risks and inability to eliminate leaching contamination at the source associated with existing polymer blending modification methods, this invention provides a graft-modified polyvinyl alcohol, its preparation method, and a small-molecule polyol-free PVA optical film obtained therefrom. This invention grafts hydroxyalkyl acrylate monomers onto the PVA backbone, covalently anchoring the plasticizing side chains to the PVA backbone, fundamentally preventing the leaching and migration of plasticizing components. Simultaneously, intermolecular hydrogen bonds between the side-chain hydroxyl groups and the PVA backbone hydroxyl groups regulate the interchain free volume, ensuring the tensile flexibility of the film.
[0010] To achieve the above objectives, in a first aspect, the present invention provides a grafted modified polyvinyl alcohol, comprising a polyvinyl alcohol backbone and a poly(hydroxyalkyl acrylate) side chain grafted onto the polyvinyl alcohol backbone.
[0011] The number of alkyl carbon atoms corresponding to the hydroxyalkyl group in the polyacrylate hydroxyalkyl ester side chain is 2 to 12; the mass fraction of the polyacrylate hydroxyalkyl ester side chain is 1% to 15% based on the total dry weight of the grafted modified polyvinyl alcohol.
[0012] Furthermore, the number of alkyl carbon atoms in the hydroxyalkyl group exhibits a gradient matching relationship with the mass fraction of the side chain:
[0013] When the number of alkyl carbon atoms in the hydroxyalkyl group is 2 to 6, the mass fraction of the hydroxyalkyl polyacrylate side chain is 7% to 15%.
[0014] When the number of alkyl carbon atoms in the hydroxyalkyl group is 6 to 10, the mass fraction of the hydroxyalkyl polyacrylate side chain is 3% to 8%.
[0015] When the number of alkyl carbon atoms in the hydroxyalkyl group is 10 to 12, the mass fraction of the hydroxyalkyl polyacrylate side chain is 1% to 4%.
[0016] The principle is as follows: short side chains have excellent compatibility with the polyvinyl alcohol matrix, low steric hindrance, and a high grafting rate will not cause phase separation, thus fully exerting the plasticizing effect. As the number of alkyl carbons in the side chains increases, the hydrophobicity and steric hindrance of the side chains increase simultaneously, requiring a corresponding reduction in the grafting rate to maintain the homogeneity of the system and avoid increased haze and uneven dyeing. By gradient matching of side chain length and grafting rate, the excellent optical uniformity and iodine dyeing compatibility of the film are maintained while ensuring the plasticizing effect.
[0017] The degree of polymerization of the polyvinyl alcohol backbone is 1700~4000, preferably 2200~3600; the degree of hydrolysis is 98.5%~100%, preferably 99.2%~99.9%.
[0018] Furthermore, the average degree of polymerization of a single side chain of the poly(hydroxyalkyl) acrylate is 1 to 300, preferably 5 to 100. If the degree of polymerization of the side chain is too low (<1), there is no grafting plasticizing effect; if the degree of polymerization is too high (>300), the hydrophobicity of the side chain accumulates, leading to intramolecular curling, which reduces the compatibility with the PVA aqueous phase and easily causes an increase in film surface haze.
[0019] The hydroxyalkyl polyacrylate grafted side chains are homopolymer side chains without α-methyl substitution, and the end of the side chains has an active hydroxyl group that can participate in iodide ion complexation. The grafted modified side chains do not contain methyl groups, excluding polyvinyl alcohol-g-polyhydroxyalkyl methacrylate, to ensure compatibility with the aqueous system.
[0020] Secondly, this invention provides two industrialization adaptation paths: Method 1: intermittent aqueous solution graft polymerization; Method 2: continuous aqueous phase reactive extrusion graft polymerization.
[0021] Method 1 includes the following steps:
[0022] S1. Disperse polyvinyl alcohol resin in deionized water and heat it to 70℃~80℃ to allow the polyvinyl alcohol to swell completely, forming a polyvinyl alcohol suspension system;
[0023] S2. Add surfactant, initiator aqueous solution and hydroxyalkyl acrylate monomer sequentially to polyvinyl alcohol aqueous solution, and carry out graft polymerization reaction under pressure at 80℃~140℃ and under inert gas (such as nitrogen) protection for 2~8 hours;
[0024] S3. After the reaction is complete, a grafted modified polyvinyl alcohol aqueous solution is obtained.
[0025] Method two is an aqueous continuous reactive extrusion process: using a pre-dissolved homogeneous aqueous solution of PVA as the feed matrix, the initiator dispersion, monomer mixing, and grafting reaction are completed during the continuous conveying process of a twin-screw extruder. The specific steps are as follows:
[0026] S1. Pre-dissolution process: Add water-washed PVA resin and a small amount of nonionic surfactant to a jacketed heating dissolution vessel, add deionized water in proportion, swell at room temperature for 30 minutes, then raise the temperature to 80℃~95℃, stir at constant temperature for 2h~3h until a paste is formed, and prepare a PVA aqueous solution with a mass fraction of 20%~30%.
[0027] S2. Continuous grafting process: PVA aqueous solution is continuously fed into the main feed port of the twin-screw extruder via a high-precision metering pump; along the material advance direction of the screw, a water-soluble initiator aqueous solution is injected before the first mixing section, and an acrylate hydroxyalkyl ester monomer is injected before the second mixing section; the material is rapidly and uniformly mixed under the strong shearing action of the screw, the temperature of each section of the extruder is controlled at 95℃~115℃, a back pressure valve is set at the end of the barrel to maintain a slight positive pressure to avoid boiling of the aqueous phase, the total residence time of the material is 5~15min, and graft copolymerization is completed simultaneously during the conveying process.
[0028] S3. Discharge devolatilization: The material after the reaction is completed is extruded through the discharge port at the end of the extruder and enters the vacuum devolatilization tank to remove trace amounts of residual monomers. After cooling to 95°C, the grafted modified polyvinyl alcohol aqueous solution is obtained directly.
[0029] Using either method one or method two, the polyvinyl alcohol resin is dispersed and cleaned with deionized water before grafting modification, and the water content after cleaning is 45%~65%.
[0030] After the grafting reaction is completed using Method 1 or Method 2, in order to avoid residual initiators and low-molecular-weight byproducts causing film surface defects, yellowing, or affecting iodine dyeing performance during subsequent casting film formation, the grafted modified polyvinyl alcohol aqueous solution needs to be purified to remove residual initiators and oligomer byproducts.
[0031] The following purification methods can be selected:
[0032] Ion exchange resin method: The grafting solution is cooled to 60℃~70℃ and passed through anion exchange resin column and cation exchange resin column in sequence to adsorb and remove ionic impurities generated by the decomposition of persulfate initiators.
[0033] Activated carbon adsorption method: Add 0.5%~2% powdered activated carbon to the grafting solution, stir at 50℃~70℃ for 1h~2h for adsorption, and then filter to remove carbon residue. This can simultaneously decolorize and deodorize.
[0034] Precipitation redissolution method: The grafting solution is added dropwise to a large amount of anhydrous ethanol to precipitate, the precipitate is collected by filtration and then dried under vacuum, and then redissolved in deionized water to prepare a solution.
[0035] The purified grafting solution is directly adjusted to the target solid content, which is the casting solution.
[0036] The water-soluble initiator is selected from one or more of potassium persulfate, ammonium persulfate, sodium persulfate, and the Fe²⁺-H₂O₂ system, and the amount added is 0.01% to 1.0% of the dry weight of polyvinyl alcohol. The initiator decomposes under heating conditions to generate free radicals, which abstract hydrogen atoms from the methylene groups on the PVA backbone to form PVA macromolecular free radicals, thereby initiating the graft polymerization of hydroxyalkyl acrylate monomers. The surfactant is selected from one or more of tallow amine polyoxyethylene ether, laurate diethanolamide, octyl salicylate, oleate diethanolamide, stearamide, and sodium dodecylbenzenesulfonate, and the amount added is 0.01% to 0.05% of the dry weight of polyvinyl alcohol. The addition of the surfactant can reduce the interfacial tension of the solution system and promote the uniform dispersion of PVA resin particles and hydroxyalkyl acrylate in the aqueous phase.
[0037] In this invention, the hydroxyalkyl polyacrylate side chain is covalently linked to the PVA backbone, forming a "chemically anchored" plasticizing structure. Numerous hydroxyl groups on the side chain form intermolecular hydrogen bonds with the hydroxyl groups on the PVA backbone, widening the gaps between PVA molecular chains, increasing free volume, and replacing the plasticizing effect of small-molecule polyols, thereby improving the film's elongation at break. The gradient matching of side chain length and grafting rate further optimizes the balance between plasticizing efficiency and optical performance: short side chains with high grafting maximize the plasticizing effect without sacrificing optical performance; long side chains with low grafting utilize the flexibility of the side chains to achieve limited plasticizing while avoiding microphase separation caused by excessive hydrophobic side chains, ensuring that products across the entire carbon number range meet the haze and transmittance requirements of optical films.
[0038] Compared to the ethylene-modified PVA route, where ethylene units are randomly distributed in the copolymer chain and lack the ability to complex iodide ions, there is a risk of uneven dyeing during polarizer manufacturing. In contrast, the hydroxyalkyl monomer used in this invention introduces long-chain alkyl groups with plasticizing effects, and its terminal hydroxyl groups can also complex iodide ions, making it more suitable for the trend towards thinner PVA optical films and lower dissolution. Furthermore, compared to the composite plasticizing route, the boric acid generated from the hydrolysis of borate esters only forms a complex with the polyol, which is a dynamic equilibrium system. During prolonged hot water immersion, the complex gradually dissociates, and the small molecule polyol is still slowly released. This invention anchors the plasticizing side chain to the PVA main chain through covalent bonds, eliminating dissociation equilibrium. The plasticizing component is permanently fixed to the polymer chain, significantly reducing dissolution in principle.
[0039] Thirdly: A polyvinyl alcohol optical film without small molecule polyol plasticization is provided.
[0040] The casting solution prepared from the purified grafted modified polyvinyl alcohol or its aqueous solution is used to form a film by casting. No small molecule polyol plasticizers such as glycerol, ethylene glycol, or propylene glycol are added to the casting solution.
[0041] The thickness of the optical film is 20μm~60μm;
[0042] The optical film has a dry tensile elongation at break of ≥420%, a tensile strength of 70MPa~80MPa, a dissolution rate of ≤300 mg / m2 after soaking in 40℃ warm water for 2 hours, a haze of ≤1.0%, and a transmittance of ≥91.5%.
[0043] The total solids content of the casting solution is 20wt%~30wt%. The casting solution is subjected to vacuum degassing, T-die casting, casting roller drying, mirror heating roller group heat setting, oven heat treatment, and winding to obtain an optical film with a film thickness of 20μm~60μm.
[0044] Fourth aspect: Provide a liquid crystal polarizer
[0045] Using the aforementioned PVA optical film as the polarizing base film, the product was prepared sequentially through swelling, iodine staining, longitudinal stretching, color fixing, and lamination with a TAC protective film. Because no small-molecule plasticizers leach from the optical film, the replacement cycle of the production bath is extended, and the polarization uniformity of the product is significantly improved.
[0046] In the above technical solution, the plasticizing side chain of the present invention is covalently anchored to the PVA main chain, and cannot migrate and dissolve in hot water or iodine dyeing bath, which greatly reduces the amount of dissolution after entering the water, thereby alleviating the problem of turbidity of the bath and reducing the consumption of iodine raw materials and the frequency of waste liquid replacement; in addition, by controlling the free volume between PVA chains through the long-chain alkyl groups in the grafted side chain, the tensile strength can be equal to or even better than the performance of traditional films plasticized with small molecule polyols, and is directly compatible with existing polarizer manufacturing processes.
[0047] This invention sets the grafting rate range based on the carbon chain length differences of the hydroxyalkyl side chains: a high grafting rate of 7%~15% is used for short side chains (C2~C6) to enhance the plasticizing effect; a medium grafting rate of 3%~8% is used for medium-long side chains (C6~C10) to balance plasticizing and compatibility; and a low grafting rate of 1%~4% is used for long side chains (C10~C12) to ensure optical uniformity. Through the synergistic control of carbon chain length and grafting density, the flexibility, optical properties, and dyeing characteristics of the film can be flexibly adjusted within a wide range to adapt to the process requirements of polarizers of different specifications.
[0048] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation
[0049] Uniform specifications for raw materials:
[0050] Polyvinyl alcohol resin: degree of polymerization 2800, degree of alcoholysis 99.8%;
[0051] Polymer monomer: hydroxyalkyl acrylate, chemical purity ≥98%;
[0052] Surfactant: Lauric acid diethanolamide, chemical purity ≥95%;
[0053] Initiator: Potassium persulfate, analytical grade;
[0054] Deionized water: conductivity ≤ 5 μS / cm.
[0055] General preparation process for grafted modified PVA:
[0056] Process A: Batch aqueous solution graft polymerization (reactor method)
[0057] S1. Add lauric acid diethanolamide (0.01% of the dry weight of PVA) and water-washed PVA resin to deionized water in sequence according to the formula. Swell at room temperature for 30 min, then heat to 75℃ and stir to swell for 2 h to obtain a PVA suspension with a mass fraction of 20%.
[0058] S2. Purge oxygen into the reactor with nitrogen for 30 minutes, then add potassium persulfate initiator aqueous solution (0.05% of the dry basis of PVA), and stir for 10 minutes to disperse evenly;
[0059] S3. Add hydroxyalkyl acrylate monomer according to the designed ratio and react at 110℃ for 6 hours;
[0060] S4. After the reaction is complete, an aqueous solution of grafted modified polyvinyl alcohol is obtained. Then, the solution is purified by precipitation redissolution. The grafted solution is added dropwise to a large amount of anhydrous ethanol to precipitate the precipitate. The precipitate is collected by filtration and then dried under vacuum.
[0061] Process B: Continuous aqueous reactive extrusion graft polymerization
[0062] S1. Pre-dissolution: Add water-washed PVA resin and lauric acid diethanolamide (addition amount is 0.01% of the dry basis of PVA) to a jacketed heating dissolution vessel, add deionized water, swell at room temperature for 30 min, then heat to 95℃ and stir for 3 h to prepare a 20% PVA aqueous solution.
[0063] S2. Continuous Grafting: A co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 is used, with 12 temperature control zones, and temperatures of 95℃, 95℃, 97℃, 99℃, 106℃, 110℃, 108℃, 106℃, 100℃, 98℃, 95℃, and 95℃ respectively. The back pressure at the end of the barrel is set to 0.2MPa. PVA aqueous solution is continuously fed into the main feed inlet at a flow rate of 12kg / h via a metering pump. Potassium persulfate initiator aqueous solution (0.05% of the dry weight of PVA) is injected at 1 / 4 of the screw length from the feed inlet, and hydroxyalkyl acrylate monomer is injected at 1 / 2 of the screw length from the feed inlet. The total residence time of the material in the barrel is approximately 8 minutes, and the mixing and grafting reactions are completed simultaneously.
[0064] S3. Deviation and purification: The extruded material enters a vacuum devolatilization tank to remove residual monomers, resulting in a grafted modified polyvinyl alcohol aqueous solution. The solution is then purified by precipitation and redissolution. The grafted solution is dripped into a large amount of anhydrous ethanol to precipitate the material. The precipitate is collected by filtration and then vacuum dried.
[0065] The degree of polymerization of the side chains can be controlled by adjusting the amount of initiator and the monomer dropping rate: increasing the amount of initiator and adding the monomer all at once results in a lower degree of polymerization of the side chains; decreasing the amount of initiator and adding the monomer slowly results in a higher degree of polymerization of the side chains. In the following examples and comparative examples, the average degree of polymerization of the side chains is approximately 45-55.
[0066] General manufacturing process for PVA optical films:
[0067] Deionized water and lauric acid diethanolamide (added at 0.02% of the dry weight of the modified PVA resin) were added to a dissolving vessel. The purified grafted modified PVA raw material was collected and added to the dissolving vessel. Nitrogen gas was introduced at 130℃~150℃ for 10 h to prepare a casting solution with a solid content of 23%~28%. The addition of surfactants reduces the interfacial tension of the solution system, thereby giving the casting solution the required leveling and release properties during the coating process. After dissolution, the film was degassed under vacuum at -0.02MPa and 95℃ for 90 min. The film was then conveyed to a T-die via a screw and uniformly cast onto a 92℃ chrome-plated mirror casting roller for pre-drying. Finally, the film was heat-treated in an oven at 120℃ for 3 min and then wound up to obtain a PVA optical film with a thickness of 30μm±1μm.
[0068] General testing and characterization methods:
[0069] 1. Grafting Rate Test: Quantitative characterization was performed using ¹H-NMR. The grafted polyvinyl alcohol samples were purified (using deuterated DMSO as solvent, concentration 20 mg / mL~50 mg / mL), and ¹H-NMR spectra were acquired at room temperature. Chemical shifts were calibrated using solvent peaks. The grafting rate was estimated based on the proportion of characteristic resonance peak areas of alkyl hydrogen atoms on the acrylate.
[0070] 2. Elongation at break: Tested using a universal electronic tensile testing machine according to HG / T 4185-2022 and GB / T 12683-2009 standards. The specimen width was 15 mm, the gauge length was 100 mm, the tensile rate was 500 mm / min, and the average value of 5 specimens was taken.
[0071] 3. Dissolution rate:
[0072] S1. Cut three 10×10cm optical film samples and soak them in 500ml of 40℃ pure water for 4 hours to prepare an extract.
[0073] S2. Add 50 ml of 40 g / L boric acid solution to a 100 ml volumetric flask, then add 10 ml of iodine-potassium iodide colorimetric reagent, then add 10 ml of extraction solution, and dilute to 100 ml with pure water. Shake well and let stand at room temperature in the dark for 20 minutes.
[0074] S3. Preparation of blank sample: Add 50 ml of 40 g / L boric acid solution to a 100 ml volumetric flask, then add 10 ml of iodine-potassium iodide colorimetric reagent, dilute to 100 ml with pure water, shake well, and let stand at room temperature in the dark for 20 minutes.
[0075] S4. Shake the blank sample (which has been left to stand for 20 minutes) well and add it to the cuvette. Wipe the outside of the cuvette dry and zero the temperature. Shake the sample (which has been left to stand for 20 minutes) well and add it to the cuvette. Wipe the outside of the cuvette dry and read the absorbance at 680 nm. Calculate the concentration using the standard curve equation. The amount of sample dissolved can be obtained using the following formula.
[0076] ,
[0077] x: Sample dissolution amount – in milligrams per square meter (mg / m²); c: Extract concentration – in micrograms per milliliter (ug / ml). Take the average value of 3 samples.
[0078] 4. Haze: The haze was measured using an integrating sphere spectrophotometer according to GB / T 2410-2008 standard, and the average value of three samples was taken.
[0079] Example 1 (Aqueous Solution Method)
[0080] Modified PVA resin was prepared using process A, with hydroxyethyl acrylate as the grafting monomer. The monomer feed amount was 11% of the dry weight of PVA, and the measured grafting rate was 9.2%. Subsequently, PVA optical films were manufactured using the general PVA optical film preparation process described above.
[0081] Example 2 (Aqueous Solution Method)
[0082] Modified PVA resin was prepared using process A, with hydroxybutyl acrylate as the grafting monomer. The monomer feed amount was 10% of the dry weight of PVA, and the measured grafting rate was 8.3%. Subsequently, PVA optical films were manufactured using the general PVA optical film preparation process described above.
[0083] Example 3 (Aqueous Solution Method)
[0084] Modified PVA resin was prepared using process A, with hydroxyhexyl acrylate as the grafting monomer. The monomer feed amount was 9% of the dry weight of PVA, and the measured grafting rate was 7.5%. Subsequently, PVA optical films were manufactured using the general PVA optical film preparation process described above.
[0085] Example 4 (Aqueous Solution Method)
[0086] Modified PVA resin was prepared using process A, with hydroxydecyl acrylate as the grafting monomer. The monomer feed amount was 6% of the dry weight of PVA, and the measured grafting rate was 4.1%. Subsequently, PVA optical films were manufactured using the general PVA optical film preparation process described above.
[0087] Example 5 (Aqueous Solution Method)
[0088] Modified PVA resin was prepared using process A, with hydroxydodecaacrylate as the grafting monomer. The monomer feed amount was 4% of the dry weight of PVA, and the measured grafting rate was 2.2%. Subsequently, PVA optical films were manufactured using the general PVA optical film preparation process described above.
[0089] Example 6 (Aqueous Phase Reactive Extrusion Method)
[0090] Modified PVA resin was prepared using process B, with hydroxyhexyl acrylate as the grafting monomer at 8% of the dry weight of PVA. Ammonium persulfate was used as the initiator at 0.1% of the dry weight of PVA, and the measured grafting rate was 7.2%. Subsequently, PVA optical films were manufactured using the general PVA optical film preparation process described above.
[0091] Comparative Example 1 (pure PVA, no plasticizers, no grafting)
[0092] No grafting modification was performed, no plasticizers were added, and the rest of the preparation process was the same as in Example 3.
[0093] Comparative Example 2 (Traditional Glycerin Small Molecule Plasticizing System)
[0094] Without grafting modification, 12% glycerol by dry weight of PVA was added as a plasticizer, and the rest of the process was the same as in Example 3.
[0095] Comparative Example 3 (physical blend system, 8% hydroxyhexyl polyacrylate)
[0096] Without grafting modification, 8% by dry weight of polyhydroxyhexyl acrylate (number average molecular weight 42000) was added for physical blending, without adding small molecule polyols; the rest of the process was the same as in Example 3.
[0097] The test results of the above embodiments and comparative examples are compared in Table 1 below:
[0098] Table 1 Comparison of test results between the examples and the comparative examples
[0099] Comparing Examples 1-5, it can be seen that the plasticizing effect is jointly determined by the length of the side chain alkyl group and the grafting rate, and not solely by the grafting rate. Short alkyl high grafting (Example 1, C2, 8.2%): Relying on a high grafting density to provide sufficient plasticizing sites, the elongation at break reached 411%, proving that short side chains can also achieve good plasticizing through quantity accumulation; Medium-short alkyl moderate grafting (Example 3, C6, 7.5%): The side chain length and grafting density achieved optimal matching, resulting in the highest plasticizing efficiency and an elongation at break of 453%, the highest among all groups using the aqueous solution method, demonstrating the synergistic gain of side chain length and grafting rate; Long alkyl low grafting (Example 5, C12, 1.9%): Although the grafting rate was only about 27% of that in Example 1, the number of alkyl carbons in a single side chain was 6 times that of C2. The spatial occupancy effect of the long alkyl chain significantly increased the free volume between the PVA main chains, thus the elongation at break still reached 394%, basically at the same level as the short alkyl high grafting system, and did not decrease significantly due to the low grafting rate.
[0100] The elongation at break of the grafted modified systems in Examples 1-6 all exceeded 390%, comparable to or even better than the comparative 2-glycerol system. Example 3 (hydroxyhexyl acrylate grafting) reached 453%, and Example 6 (aqueous reactive extrusion) reached 472%, fully demonstrating that the hydroxyalkyl acrylate side chains can effectively control the free volume between PVA chains through the free slippage of the hydroxyalkyl branches under external force, completely replacing small molecule polyols to achieve efficient plasticization. Simultaneously, the tensile strength of the grafted systems ranged from 70 MPa to 85 MPa, significantly higher than the comparative 2-glycerol system (63.8 MPa). This indicates that the covalent grafting plasticization method, while improving flexibility, weakens the bulk mechanical strength of PVA far less than small molecule plasticizers, making it more beneficial for the high-ratio stretching process of polarizers.
[0101] Comparative Example 2 shows that the soluble content of the glycerol small molecule plasticized system is as high as 557 mg / m². A large amount of small molecule polyols rapidly diffuse and migrate out during hot water immersion, which is the root cause of iodine dyeing bath contamination and frequent bath replacement. Comparative Example 3 shows that the soluble content of the physical blend system is also as high as 421 mg / m². The free polyhydroxyhexyl acrylate is only bound to PVA through intermolecular hydrogen bonds and has no chemical bond constraint. It will continue to dissolve during hot water immersion and cannot eliminate the contamination.
[0102] In contrast, the dissolution rates of the grafted modified systems in Examples 1-6 were all controlled below 250 mg / m², with Example 6 (aqueous reactive extrusion method) reaching as low as 198 mg / m², only 39% of the glycerol system in Comparative Example 2 and 47% of the blend system in Comparative Example 3. This significant reduction in dissolution rate stems from two aspects: first, the plasticizing side chains are covalently anchored to the PVA backbone, eliminating the presence of free, migratable plasticizing components and thus preventing plasticizer dissolution at the molecular level; second, the grafting reaction causes some low-molecular-weight PVA segments to combine with the side chains to form high-molecular-weight components, further reducing the hot water dissolution of low-molecular-weight PVA and addressing the bath contamination problem at its source.
[0103] The haze of the physical blend system in Comparative Example 3 was as high as 0.97%, and the visible light transmittance was only 89.08%, which was far inferior to the other groups. The reason is that the polyhydroxyhexyl acrylate with a number average molecular weight of 42,000 and PVA are only physically blended. The high molecular weight component has limited compatibility with the PVA matrix, which easily forms a micro-phase separation structure, causing light scattering and failing to meet the application requirements of high-end optical films.
[0104] Examples 1-6 show that the grafted modified systems are all single-component homogeneous copolymers with no risk of phase separation. The haze ranges from 0.15% to 0.55%, and the visible light transmittance is all above 91.5%, demonstrating excellent optical performance. The short carbon chain side chains (C2-C6) exhibit even lower haze (<0.30% in Examples 1-3), comparable to or better than the comparative example 2-glycerol system. As the alkyl carbon chain length increases to C10 and C12 (Examples 4-5), the hydrophobicity of the side chains increases, and the haze slightly increases, but remains far lower than that of the physically blended system, verifying the rationality of limiting the alkyl carbon number range to 2-12 in this invention.
[0105] Short side chains (C2~C6) have low steric hindrance, and the terminal hydroxyl groups of the side chains can assist in the complexation of iodide ions, resulting in minimal interference with boric acid crosslinking. Although medium and long side chains (C10~C12) have longer carbon chains, their grafting rate is low (≤4%), most of the hydroxyl groups on the main chain remain in a free state, and the side chains have a flexible suspended structure, which does not form a continuous steric barrier. Therefore, the influence on the uniformity of iodine staining and the boric acid crosslinking network is also controllable.
[0106] Example 6 (aqueous reactive extrusion) and Example 3 (batch aqueous solution method) use the same monomers and feed ratios, and their performance is similar, but each has its own emphasis: the reactive extrusion method has a higher elongation at break (469% vs 433%) and a lower dissolution rate (198 mg / m² vs 237 mg / m²), due to the strong shear of the screw during continuous extrusion, which makes the grafting reaction more uniform and reduces low-molecular-weight byproducts. The aqueous reactive extrusion method completes continuous grafting in a low-temperature aqueous environment of 95℃~110℃, resulting in stable product quality; at the same time, the continuous production efficiency is higher than that of batch reactors, and the product can be connected to the subsequent casting process after ion exchange resin treatment, resulting in a shorter process flow and suitability for large-scale industrial mass production. The batch aqueous solution method can be directly integrated into existing PVA dissolution production lines with low equipment modification costs. Both processes have their advantages.
[0107] The above results fully verify the comprehensive advantages of the grafting modification scheme of the present invention in four aspects: plasticizing effect, mechanical strength, dissolution control and optical performance of PVA optical film, and solve the industry pain points that the existing technology cannot achieve simultaneously.
Claims
1. A grafted modified polyvinyl alcohol, comprising a polyvinyl alcohol backbone, characterized in that, The grafted modified polyvinyl alcohol uses polyhydroxyalkyl acrylate as the grafted side chain, and the grafted side chain is covalently linked to the polyvinyl alcohol main chain, having the structure of formula (1): Equation (1) Where, a represents the number of alkyl carbon atoms corresponding to the hydroxyalkyl group in the hydroxyalkyl grafted side chain of the polyacrylate, which is 2 to 12. The mass fraction of the hydroxyalkyl polyacrylate grafted side chain is 1% to 15% based on the total dry weight of the grafted polyvinyl alcohol.
2. The grafted modified polyvinyl alcohol according to claim 1, characterized in that, Based on the total dry weight of the grafted modified polyvinyl alcohol, when the number of alkyl carbon atoms in the hydroxyalkyl group is 2 to 6, the mass fraction of the grafted side chain of the polyacrylate hydroxyalkyl ester is 7% to 15%; when the number of alkyl carbon atoms in the hydroxyalkyl group is 6 to 10, the mass fraction of the grafted side chain of the polyacrylate hydroxyalkyl ester is 3% to 8%; and when the number of alkyl carbon atoms in the hydroxyalkyl group is 10 to 12, the mass fraction of the grafted side chain of the polyacrylate hydroxyalkyl ester is 1% to 4%.
3. The grafted modified polyvinyl alcohol according to claim 1 or 2, characterized in that, The degree of polymerization of the polyvinyl alcohol backbone is 1700~4000, preferably 2200~3600; the degree of hydrolysis is 98.5%~100%, preferably 99.2%~99.9%.
4. The grafted modified polyvinyl alcohol according to any one of claims 1-3, characterized in that, The hydroxyalkyl polyacrylate grafted side chain is a homopolymer side chain without α-methyl substitution, and the end of the side chain has an active hydroxyl group that can participate in iodide ion complexation.
5. The grafted modified polyvinyl alcohol according to any one of claims 1-4, characterized in that, The average degree of polymerization of a single side chain of the hydroxyalkyl polyacrylate grafted side chain is 1 to 300, preferably 5 to 100.
6. A method for preparing graft-modified polyvinyl alcohol as described in any one of claims 1-5, characterized in that, The preparation method employs an intermittent aqueous solution graft polymerization method, including: (1) Disperse the cleaned and purified polyvinyl alcohol resin in deionized water and heat it to 70℃~80℃ to allow the polyvinyl alcohol to fully swell; (2) Add hydroxyalkyl acrylate monomer, water-soluble initiator and surfactant to polyvinyl alcohol suspension, and carry out graft copolymerization reaction for 2 to 8 hours at 80℃~140℃ under inert gas protection to obtain graft modified polyvinyl alcohol aqueous solution.
7. A method for preparing graft-modified polyvinyl alcohol as described in any one of claims 1-5, characterized in that, The preparation method employs a continuous aqueous phase reactive extrusion graft polymerization method, including: (1) Pre-dissolution: Water-washed polyvinyl alcohol resin and surfactant are added to a dissolving vessel, deionized water is added, and the temperature is raised to 80℃~100℃ and stirred to dissolve, so as to prepare a homogeneous aqueous solution of polyvinyl alcohol with a mass fraction of 20%~30%; (2) Continuous grafting: Polyvinyl alcohol aqueous solution is continuously pumped to the feed port of twin-screw extruder via metering pump; along the material conveying direction of the extruder, water-soluble initiator aqueous solution and hydroxyalkyl acrylate monomer are injected sequentially through the side injection port; the temperature of each section of the extruder is controlled at 90℃~115℃, the system is operated under pressure, and the total residence time of the material in the barrel is 5~15min to complete the graft copolymerization reaction.
8. The preparation method according to claim 6 or 7, characterized in that, In step (1), the polyvinyl alcohol resin is dispersed and cleaned with deionized water before grafting modification, and the water content after cleaning is 45%~65%.
9. The preparation method according to claim 6 or 7, characterized in that, In step (2), after the reaction is completed, the grafted modified polyvinyl alcohol aqueous solution is purified to remove residual initiator and low molecular weight byproducts; the purification treatment is selected from one or more combinations of ion exchange resin adsorption method, activated carbon adsorption method, and precipitation redissolution method.
10. The preparation method according to claim 6 or 7, characterized in that, In step (2), the water-soluble initiator is selected from one or more of potassium persulfate, ammonium persulfate, sodium persulfate, and Fe²⁺-H₂O₂ system, and the amount added is 0.01% to 1.0% of the dry basis mass of polyvinyl alcohol.
11. The preparation method according to claim 6 or 7, characterized in that, The surfactant is selected from one or more of the following: tau ester amine polyoxyethylene ether, lauric acid diethanolamide, octyl salicylate, oleic acid diethanolamide, stearamide, and sodium dodecylbenzene sulfonate, and the amount added is 0.01% to 0.05% of the dry basis mass of polyvinyl alcohol.
12. A polyvinyl alcohol optical film without small molecule polyol plasticizing, characterized in that, It is prepared by casting a film solution containing grafted modified polyvinyl alcohol as described in any one of claims 1-5 through casting, drying and molding; the casting film solution does not contain small molecule polyol plasticizers such as glycerol, ethylene glycol, and propylene glycol.
13. The optical film according to claim 12, characterized in that, The thickness of the optical film is 20μm~60μm.
14. The optical film according to claim 12 or 13, characterized in that, The optical film has a dry tensile elongation at break of ≥420% and a tensile strength of 70MPa~80MPa.
15. The optical film according to any one of claims 12-14, characterized in that, The dissolution rate after soaking in 40℃ warm water for 2 hours is ≤300 mg / m2, the haze is ≤1.0%, and the transmittance is ≥91.5%.
16. A thin-film transistor polarizer, characterized in that, The polyvinyl alcohol optical film without small molecule polyol plasticization as described in any one of claims 12-15 is used as the polarizing base film.